2002
DOI: 10.2214/ajr.179.3.1790735
|View full text |Cite
|
Sign up to set email alerts
|

Stomal Metastases Complicating Percutaneous Endoscopic Gastrostomy: CT Findings and the Argument for Radiologic Tube Placement

Abstract: CT showed lobulated soft tissue involving the entire abdominal wall PEG tract in all proven cases. CT is an effective method for evaluation because the tumor burden lies predominately in the abdominal wall and not at the entry or exit site. The stomal implant is often the only site of metastatic disease at presentation. In general, CT findings of mildly increased soft tissue along the PEG tract are nonspecific, but a lobulated mass is highly suspicious for tumor implantation, especially if the one-sided thickn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 14 publications
0
16
0
1
Order By: Relevance
“…Schrag [7] reported an incidence of less than 1% and Adelson [22] could only find 22 cases in a Medline search performed in 2004. Some authors recommend avoiding PEG insertion in patients with oropharyngeal or esophageal cancer [23]. Other authors proposed to use laparoscopy or open gastrostomy, or the push instead of the pull technique, to avoid tumor cell seeding [22].…”
Section: Complicationsmentioning
confidence: 99%
“…Schrag [7] reported an incidence of less than 1% and Adelson [22] could only find 22 cases in a Medline search performed in 2004. Some authors recommend avoiding PEG insertion in patients with oropharyngeal or esophageal cancer [23]. Other authors proposed to use laparoscopy or open gastrostomy, or the push instead of the pull technique, to avoid tumor cell seeding [22].…”
Section: Complicationsmentioning
confidence: 99%
“…Patient age, whether old or young age, was not a risk factor for stomal metastases (mean age 59.0 ± 10.0 yr, N = 43, not reported in (24); age distribution similar for (4) Longer duration for implanted cancerous cell(s) to multiply and become grossly evident at stoma * References include: (2,7,12,15,20,(24)(25)(26)(27)30,(33)(34)(35)40,41,43). * * Includes 27 receiving PEG before any cancer therapy, and 7 undergoing PEG after known local recurrence following ablative cancer therapy (surgery, chemotherapy, or radiotherapy).…”
Section: Rejected Risk Factorsmentioning
confidence: 99%
“…The literature is mostly scat- 1 One review article published in 2004 reviewed one single factor, the relation between cancer stage and stomal metastases in 30 reported patients (4). tered as single case reports with the largest published series comprising only three new cases (2); is often published in obscure journals; and lacks a recent comprehensive clinical review with the largest previous review comprising only 25 cases (3). 1 The literature also lacks a systematic analysis of risk factors for this complication, which would provide a rational strategy for reducing the risk of this life-threatening endoscopic complication.…”
Section: Introductionmentioning
confidence: 99%
“…Although the incidence of PEG site metastases is low, estimated at 0.5 – 3% [2,4,13,50], survival outcomes indicate that this complication carries a grave prognosis. The estimated survival rate of 12.9% shown in the present review, although seemingly better than that reported for other sites of distant metastatic disease in HNSCC (1–6.5%) [51,52], is likely a gross overestimation as available follow up in the case reports reviewed was well below five years.…”
Section: Discussionmentioning
confidence: 99%